Overcoming efficiency and stability limits in water-processing nanoparticular organic photovoltaics by minimizing microstructure defects - Chen Xie (Nature Portfolio, 2018)
Water-based semiconducting polymer nanoparticles are eco-friendly and non-toxic but their performance suffers from the surfactants. Here Xie et al. design an approach to minimize the amount of residual surfactant in these nanoparticles and make high-efficiency and stability solar cells.